Risk Factors and Maternal Complications of Placental Abruption in Third Trimester of Pregnancy (Journal of Fatima Jinnah Medical University, 2018)
Background: Placental abruption, defined as the separation of the placenta from the wall of the uterus prior to the fetal delivery, accounts for about 0.4-1% of the pregnancies. Women with diagnosis of a placental abruption and stillborn infant on admission are more likely to require massive transfusions and have complications, such as acute renal failure and disseminated intravascular coagulation (DIC), compared with women having a live fetus at presentation. These high-risk pregnancies can be managed vigilantly in the antenatal period to prevent fetal and maternal complications. The objective of this study was to determine the risk factors and maternal complications in females presenting with placental abruption during third trimester of pregnancy.Patients and Methods: This cross-sectional study was conducted in the Department of Obstetrics & Gynecology, Sir Ganga Ram Hospital, Lahore from 21-7-2016 till 20-7-2017. A total of 400 females meeting the inclusion criteria were registered. Actual gestational age was calculated from 1st day of LMP. Appropriate investigations included imaging and laboratory tests. Complications were recorded. Patients were managed according to fetomaternal condition.Results: In this study, prevalence of placental abruption was found to be 2.8%. Out of 400 patients, 45.75% (n=183) were between 18-30 years of age while 54.25% (n=217) were between 31-40 years of age (mean 30.74+4.77 years) with mean gestational age of 35.5+2.94 weeks. Frequency of maternal complications in females presenting with placental abruption during third trimester of pregnancy after 28 weeks of gestation was recorded. Hypovolemic shock was observed in 27% (n=108), while renal failure was recorded in 5.5% (n=22) patients. Hypertensive disorder followed by grand-multiparity, increased maternal age and trauma are found to the most common risk factors for placental abruption in the present study as 78.5% (n=314) of the patients had hypertensive disorder, 60% (n=242) patients were multigravida, 54.25% (n=217) patients were >30 years of age and 1.5% (n=6) patients presented after trauma. Frequency of fetal complications was calculated as, 57.25% (n=229) had preterm delivery, 46.75% (n=187) neonatal ICU admissions and 10.75% (n=43) intrauterine fetal demise were noted. Other maternal complications include disseminated intravascular coagulation in 4.5% (n=18) of the patients and 0.75% (n=3) maternal mortalities were noted.Conclusion: Frequency of hypovolemic shock is significantly higher followed by renal failure in females presenting with placental abruption during third trimester of pregnancy after 28 weeks of gestation. However, every patient with placental abruption should be sorted out for the fetomaternal complications. Early diagnosis by identifications of the risk factors followed by the close follow up of the high risk patients, improvement in monitoring techniques and multidisciplinary team approach can lead to substantial improvement in fetomaternal outcome in patients with placental abruption.
Keywords: Abruptio placenta, maternal complications, hypovolemic shock, renal failure.